Becoming leaders : a practical handbook for women in engineering, science, and technology - Williams, F. Mary; Emerson, Carolyn J. (American Society of Civil Engineers, 2019)
Co-published by ASCE Press and the Society of Women Engineers If you think this is just another book about women's issues, think again. This one is different. Becoming Leaders: A Practical Handbook for Women in Engineering, Science, and Technology, Second Edition is intended for people interested in the advancement of their own careers or in the development of human resources in their organization. Information is given in a reader-friendly format with easy-to-find bulleted lists supported by current research in sociology, education, and psychology. This second edition includes new information on implicit bias, other factors affecting leadership success, the impact of social media, management of diversity and inclusion initiatives, and creating respectful workplaces. Professional women in STEM, and managers interested in their progress, will quickly recognize the context of many of the information bytes and see the application in their own workplaces. This handbook provides readers with action plan elements for achieving important goals--both personal and organizational. A sample organizational leadership skills checklist is included. Chapters can be read in any order, with roadmaps for students, career women, faculty, and managers. Written both to support career success and to encourage leadership self-awareness, Becoming Leaders is a book you'll turn to again and again for advice, for information, and most of all for inspiration.